Does Technostress Increase R&D Employees' Knowledge Hiding in the Digital Era? - Zhang, Zhengang; Ye, Baosheng; Qiu, Zhijun; Zhang, Huilin; Yu, Chuanpeng (Frontiers in Psychology, 2022)
The perspective of digital technology stress for the antecedent factor exploration of knowledge hiding continues to be seldom discussed in the digital era. Based on job demand-resource theory, this article introduces work exhaustion as a mediator variable and constructs a model that the five sub-dimensions of technostress (i.e., overload, invasion, complexity, insecurity, and uncertainty) affect knowledge hiding for R&D employees. Similarly, this study analyzes the moderation of workplace friendship as the resource buffering effect. Based on the 254 questionnaire data of the two-stage survey, it empirically tests the research model. The results show that: (1) Techno-invasion, techno-insecurity, and techno-complexity have significant positive effects on work exhaustion, and techno-invasion has the greatest effect. However, techno-overload and techno-uncertainty have no significant relationship with work exhaustion. (2) Work exhaustion plays a mediating role in the relationship among techno-invasion, techno-insecurity, techno-complexity, and knowledge hiding; however, its mediating effects among techno-overload, techno-uncertainty, and knowledge hiding are insignificant. (3) Workplace friendship negatively moderates the relationship among techno-invasion, techno-insecurity, and work exhaustion, and the mediating effects of work exhaustion in techno-invasion, techno-insecurity, and knowledge hiding. Nonetheless, its negative moderation for the relationships among techno-overload, techno-uncertainty, and work exhaustion are insignificant. Empirical results further show that workplace friendship positively moderates the relationship between techno-complexity and work exhaustion.